Analisis Kriminologi Terhadap Fenomena Bunuh Diri di Kota Gorontalo - Al amry, Ilham; Darmawati, Darmawati; Haritsa, Haritsa (Fakultas Hukum Universitas Ichsan Gorontalo, 2024)
This research aims to find the factors causing suicide and to determine theefforts to overcome suicide by the Gorontalo City Resort Police. The researchmethod used is empirical legal research, namely, legal research thatexamines implementing laws and regulations in the field. The results of thisstudy indicate that the causes of suicide in the jurisdiction of the GorontaloCity Resort Police, namely the economic factor, namely the victim is knownentangled in a large amount of debt, the romance or love factor, and thedepression factor which is a triggering factor for the decision to end life bycommitting suicide. The efforts to overcome suicide cases in Gorontalo Citycarried out by the police are by conducting socialization and counselingefforts as well as assistance efforts carried out in collaboration withpsychologists, especially for victims of attempted suicide. From the results ofthis research, the recommendation is that the government should increaseintegrated efforts in terms of growing awareness of values and recognizingforms of suicide deviations. The public can play a more active role indeveloping suicide prevention awareness as early detection of familymembers, especially those who have serious problems leading to depression